2007
DOI: 10.1097/rhu.0b013e318124a8af
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Systemic Lupus Erythematosus and Associated Comorbidities in Puerto Rico

Abstract: Objective-To determine the prevalence of systemic lupus erythematosus (SLE) and its associated comorbidities in patients from Puerto Rico using a database from a health insurance company.Methods-The insurance claims submitted by physicians in 2003 to a health insurance company of Puerto Rico were examined. Of 552,733 insured people, 877 had a diagnosis of SLE (code 710.0) per the International Classification of Diseases, Ninth Revision (ICD-9). Demographic parameters and selected comorbidities were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…We found that CRP levels were higher in females than in males, which is consistent with other studies [16,56]. Of interest, women are more prone to autoimmune diseases such as Lupus and Rheumatoid Arthritis [57,58], which are characterized by inflammation, elevated CRP [59,60], and accelerated rates of microvascular disease and atherosclerosis [61,62]. Elevated CRP in these women is also associated with cognitive impairments.…”
Section: Discussionsupporting
confidence: 90%
“…We found that CRP levels were higher in females than in males, which is consistent with other studies [16,56]. Of interest, women are more prone to autoimmune diseases such as Lupus and Rheumatoid Arthritis [57,58], which are characterized by inflammation, elevated CRP [59,60], and accelerated rates of microvascular disease and atherosclerosis [61,62]. Elevated CRP in these women is also associated with cognitive impairments.…”
Section: Discussionsupporting
confidence: 90%
“…31 There is also evidence on higher prevalence of symptomatic and subclinical hypothyroidism in SLE patients compared to controls or the general population. 32,33 In our study the medication for hypothyroidism was almost five times more common than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies that assigned a single incidence rate to all patients (1,(22)(23)(24)(25), this method assigned different rates for various age and sex categories by census tract, therefore adjusting for these variables. In the process of constructing this map, a systematic methodology for converting patient residential history from paper charts to an electronic database and subsequently to a map was also demonstrated.…”
Section: Discussionmentioning
confidence: 99%